Spectrum of Aminoglycoside Modifying Enzymes in Gram-Negative Bacteria Causing Human Infections - Lalitha Aishwarya, Kayanam Vijaya; Venkataramana Geetha, Pacha; Eswaran, Sudalai; Mariappan, Shanthi; Sekar, Uma (Journal of Laboratory Physicians, 2020)
Introduction Aminoglycosides are formidable broad-spectrum antibiotics used in clinical settings; woefully their usage has been reduced by the emergence and distribution of resistance mainly due to aminoglycoside modifying enzymes (AME).Purpose This study was performed to determine the diverse prevalence of AME and their pattern of occurrence in the clinical isolates of gram-negative bacteria. This study also aimed to detect the presence of AMEs that are prevalent in gram-positive bacteria, among gram negatives.Materials and Methods A total number of 386 clinical isolates were included in this study. Polymerase chain reaction revealed the prevalence rate of AMEs screened [aac(6′)-lb, aac(3′)-I, aac(3′)-II, aac(3′)-VI, ant(2′)-I, ant(4′)-IIb, aac(3′)-III, aac(3′)-IV, aph(2′)-Ib, aph(2′)-Ic, aph(2′)-Id, aac (6′)-Ie- aph(2′)-Ia, and aph(3′)-IIIa]. Conjugation experiment was performed for the clinical isolates which harbored any one of the AME which was prevalent in gram-positive bacteria [aph(3′)-IIIa, aac(6′)-Ie-aph(2′)-Ia].Results aac(6′)-lb is the most prevalent AME, followed by aac(3′)-I, aph(3′)-VI, aac(3′)-VI, and aac(3′)-II. The AMEs such as ant (2′)-I, ant(4′)-IIb, aac(3′)-III, aac(3′)-IV, aph(2′)-Ib, aph(2′)-Ic, and aph(2′)-Id were not established in our study isolates. The rate of prevalence of aph(3′)-IIIa, aac(6′)-Ie-aph(2′)-Ia—the AMEs encountered in gram-positive and their co-existence was 19.68% and the conjugation experiment revealed their transfer via plasmids.Conclusion This is the first report from India revealing the presence and prevalence of AMEs which are often encountered among gram-positive bacteria in gram negatives and their presence on conjugative plasmids.
Keywords: AME; conjugative plasmid; GP AME; gram-negative bacteria